THE ASSISTANCE OF THE NUMERIC CALCULATIONS FOR ESTIMATION OF REQUIRED PARAMETERS OF PHOTOREFRACTIVE CRYSTALS FOR TWO CENTER HOLOGRAPHIC RECORDING - Kilic, Mehmet; Demirbilek, Riza (YILDIZ TECHNICAL UNIV, 2010)
The dependence of the diffraction efficiency of LiNbO3 for two center holographic recording (TCHR) on time calculated by implemented computer program is compared with those obtained from the previous experimental results. The applicability of this method to other photorefractive crystals was shown in the Strontium Barium Niobat (SBN) sample. It is assumed that with the assistance of this program some unknown parameters of the photorefractive crystals can be determined by means of fitting the experimental results for TCHR.
Keywords: Two center holographic recording; LiNbO3; SBN; Engineering